The Sub-acute Effect of Lead Exposure on the Auditory Brainstem Response in Male Rats - Iraj Alimohammadi; Azadeh Ashtarinezhad; Jamileh Abolghasemi; Parvaneh Yekzamani; Batol Masruri* (Iranian Journal of Toxicology, 2019)
Background: Lead is a major environmental pollutant and can adversely affect humans and animals. There are conflicting data about the ototoxic effect of lead. This study experimentally examined the association between blood lead levels (BLL) and the subsequent hearing impairment in male rats. Methods: Twenty-two male rats were randomly categorized into experimental (exposed to lead acetate, 4 mg/kg by gavage) and control groups. We evaluated the groups by click and tone audiometric burst tests, comparing the data before and 30 days after exposure to lead acetate (4mg/kg). Also, blood samples were collected from the rats and analyzed for lead levels by graphite furnace atomic absorption spectrometry. Results: The study findings demonstrated remarkable increase in hearing threshold in the lead-exposed group, compared to the controls (p<0.0001). Also, the blood lead levels revealed a significant association of lead acetate with the hearing loss in rats. Conclusion: This study revealed that exposure to lead acetate can be damaging to hearing. However, future research is recommended to clarify the mechanism of action of lead toxicity on the auditory function at varying blood lead concentrations.